First report of Maize striatemosaic virus, a mastrevirus infecting Zea mays in Argentina - Ruiz Posse, Agustina María; Fernandez, Franco Daniel; Reyna, Pablo Gastón; Nome Docampo, Claudia; Torrico Ramallo, Ada Karina; Gimenez Pecci, María De La Paz; Rodriguez Pardina, Patricia (Wiley, 2023)
During 2021, sweet corn plants cultivated for human consumption in a 400-ha area in Santa Fe province, Argentina, showed severe virus-like symptoms, including marked dwarfism, plant deformation, nerval or internerval vein yellowing, chlorotic rings, chlorosis along leaf edges, and vein thickening (Figure 1, 2). Abundant populations of the corn leafhopper Dalbulus maidis, a vector of several pathogens (Carloni et al., 2013), were also observed (Figure 3). Ten diseased plants collected in Helvecia, Santa Fe (31°07´47´´S, 60°08´48´´W) were tested by leaf dip and serology (DAS-ELISA or PTA-ELISA) against: Maize yellow striate virus, Mal de Río Cuarto virus, Spiroplasma kunkelii, Sugarcane mosaic virus (JM isolate) (IPAVE, Córdoba, Argentina), Maize rayado fino virus (MRFV) (provided by Castillo Loayza, UNALM, Perú), Maize chlorotic mottle virus (MCMV), Maize dwarf mosaic virus (BIOREBA, Switzerland), Wheat streak mosaic virus (DSMZ, Germany), Cucumber mosaic virus, High Plains wheat mosaic virus (HPWMoV), Maize streak virus (MSV) and Sugarcane mosaic virus (SCMV) (Agdia, USA).